Analisis pengaruh harga tandan buah segar, crude palm oil, dan nilai tukar mata uang terhadap ekspor crude palm oil di Provinsi Jambi - Azzahra, Rifda; Zulgani, Zulgani; Bahri, Zainul (e-Journal Perdagangan Industri dan Moneter, 2024)
This research aims to analyze developments in FFB prices, CPO prices, exchange rates and CPO exports. Then to analyze the influence of FFB prices, CPO prices and exchange rates on CPO exports. The analytical method used is descriptive analysis and quantitative analysis. The data used in this research is secondary data with Time Series data for 2000-2023. The data sources used in this research are the Jambi Province Plantation Service, the Palm Oil Farmers Union (SPKS), the Jambi Province Central Statistics Agency, Bank Indonesia. The analysis technique used is Error Correction Model (ECM) analysis. The research results show that: (1) The development of CPO exports, FFB prices, CPO prices and exchange rates tend to fluctuate every year. (2) The FFB price and CPO price variables have a positive and significant effect on CPO exports in the long and short term. (3) The exchange rate variable has a positive but not significant effect on CPO exports in the long and short term.